Minimally invasive haemodynamic monitoring: PiCCO - Mat Nor, Mohd Basri (2013)
Resuscitation of critically ill patients in the intensive care setting is a complex process requiring the accurate measurement of haemodynamic parameters i.e. cardiac output, stroke volume variation and systemic vascular resistance. Haemodynamic monitoring data is used to optimize the balance between tissue oxygenation supply and demand and effectively combat global tissue hypoxia, shock and multi organ failure in critically ill patients. This information guides treatment and prevents morbidity and mortality. Invasive haemodynamic monitoring has been the connerstone of the care of the critically ill and haemodynamically unstable patient. Nevertheless, several concerns have been raised regarding its invasiveness and associated complications. This has led to the development of a number of less invasive technologies for cardiac output determination.